1998
DOI: 10.1016/s0895-7061(98)00150-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regulation of high blood pressure on plasma endothelin-1 levels in blacks with hypertension☆

Abstract: Plasma concentrations of immunoreactive endothelin-1 (irET-1) are significantly elevated in blacks with hypertension. In the present study, we investigated the effect of the regulation of high blood pressure on plasma irET-1 levels in black hypertensive individuals. After the initial blood samples were collected from 20 black patients with uncontrolled high blood pressure (Day 1), an intensive antihypertensive treatment was initiated, and the blood pressure and plasma irET-1 levels were monitored on days 2, 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…Prior investigations have noted increased circulating levels of ET-1 among African Americans compared to Whites among both normotensives and hypertensives (2, 30). Similar to our findings, a small study of hypertensive African Americans noted a reduction in plasma ET-1 levels following antihypertensive therapy with agents of various classes (31). Not surprisingly, treatment with an ET-1 receptor blocker results in decreases in ET-1-mediated vasoconstriction.…”
Section: Discussionsupporting
confidence: 91%
“…Prior investigations have noted increased circulating levels of ET-1 among African Americans compared to Whites among both normotensives and hypertensives (2, 30). Similar to our findings, a small study of hypertensive African Americans noted a reduction in plasma ET-1 levels following antihypertensive therapy with agents of various classes (31). Not surprisingly, treatment with an ET-1 receptor blocker results in decreases in ET-1-mediated vasoconstriction.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies reported that ET A receptor antagonism decreases collagen accumulation and improves MMP-2 activity in kidneys from stroke-prone SHRs (32) as well as decreasing fibronectin levels and MMP activity in the left ventricle of DOCA-salt hypertensive rats that display cardiac fibrosis (2). In clinical hypertension, there is a consensus that ET-1 levels are increased in patients with low-renin and salt-sensitive forms of hypertension, which is predominantly seen in the African-American population (6)(7)(8)30). In this patient population, frequent exposure to behavioral and environmental stress plays an important role in the development of hypertension (9).…”
Section: Discussionmentioning
confidence: 99%
“…In DOCA-salt hypertensive rats, enhanced myocardial remodeling and fibrosis associated with increased fibronectin, matrix metalloproteinase (MMP) activity, and proinflammatory mediators occur in the left ventricle and ET A receptor antagonism inhibits these changes (1, 2). In clinical hypertension, ET-1 is increased in African-American hypertensive patients who present with increased incidence of cardiovascular complications, including left ventricle hypertrophy and stroke (7,8). Although the exact mechanism is not clear, it has been proposed that African-Americans experience chronic sympathetic system activation due to more recurrent exposure to social and environmental stress, which contribute to the increased incidence of hypertension and related complications in this patient population (9).…”
mentioning
confidence: 99%
“…46 Plasma ET-1 concentrations that were relatively high at the beginning of the study were dramatically reduced in a manner parallel to the reduction in blood pressure. This study provided indirect evidence that ET-1 levels may rise as a consequence of hypertension and contribute to the high incidence of hypertension-related complications in blacks.…”
Section: Blacks and The Et System Plasma Et-1 Levelsmentioning
confidence: 91%